(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2022)
Background and Objectives: The global incidence of dengue has grown dramatically in recent decades affecting children and young adults mainly in tropical and subtropical countries.Dengue has a wide spectrum of clinical presentations, often with unpredictable clinical evalution and outcome. While most patients recover following a self-limiting non-severe clinical course, a small proportion progress to severe disease, mostly characterised by plasma leakage with or without haemorrhage. Methods: It is a Prospective ,observational study including 150 serologically confirmed Dengue fever in a tertiary care centre. The main objective was to study patterns of hepatopathy in dengue fever and to determine whether the patterns of hepatic involvement correlate with clinical , laboratory profile and outcome in Dengue fever according to WHO classification .Results: Younger age groups were found to be more prone to hepatopathy with 46.7 % of patients having hepatopathy (transaminases >3x UNL) belonging to ages 21-30 yrs. AST level correlates maximum with severe Dengue ,followed by abnormal PT and APTT value .AST is more useful than ALT and AST:ALT Ratio is even more reliable indicator than using the values alone.Risk factors which were statistically significant for mortality :Positive Tourniquet test, Abnormal CNS Examination, Bleeding Manifestations, and thrombocytopenia.Hepatic dysfunction Grade 3 and 4 were not directly related to mortality. Interpretation and Conclusion: Even though hepatopathy does not correlate with the severity of disease directly, its significant association with warning signs ,thrombocytopenia and bleeding manifestations make it very important factor to predict which subset of patients will develop severe Dengue fever.Timely diagnosis of hepatopathy in patients with dengue fever and its management may improve patient survival rate.